2018
DOI: 10.1111/jpy.12625
|View full text |Cite
|
Sign up to set email alerts
|

Physiological response of 10 phytoplankton species exposed to macondo oil and the dispersant, Corexit

Abstract: Culture experiments were conducted on ten phytoplankton species to examine their biological and physiological responses during exposure to oil and a combination of oil and dispersant. The species tested included a range of taxa typically found in the Gulf of Mexico such as cyanobacteria, chlorophytes, and diatoms. Cultures were exposed to Macondo surrogate oil using the water accommodated fraction (WAF), and dispersed oil using a chemically enhanced WAF (CEWAF) and diluted CEWAF, to replicate conditions follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 66 publications
4
37
0
1
Order By: Relevance
“…The arrested growth of T. pseudonana when exposed to WAF during the initial period of the growth experiment reaffirms the sensitivity of this diatom to oil as reported in Bretherton et al (2018). The F v /F m and rETR max in WAF treatments were all much lower than those in the Control treatments in the first 4 d, consistent with the exposure to oil leading to a suppression of photosynthesis in this diatom.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The arrested growth of T. pseudonana when exposed to WAF during the initial period of the growth experiment reaffirms the sensitivity of this diatom to oil as reported in Bretherton et al (2018). The F v /F m and rETR max in WAF treatments were all much lower than those in the Control treatments in the first 4 d, consistent with the exposure to oil leading to a suppression of photosynthesis in this diatom.…”
Section: Discussionsupporting
confidence: 84%
“…Commonly known as "CROSERF" (Singer et al, 2001), this method is widely accepted as the standard technique for preparing WAF. f/2 growth media was prepared using filtered sea water from the Gulf of Mexico as described in Bretherton et al (2018). Before decanting into culture vessels, the solution was filtered through a 20-mm nylon sieve to ensure that the resulting WAF media was devoid of large oil droplets.…”
Section: Experimental Designmentioning
confidence: 99%
“…Previous laboratory studies, which examined the response of individual phytoplankton strains to oil and chemically dispersed oil, have shown T . pseudonana to be a sensitive species with reduced growth rates and lowered photosynthetic activity [ 12 , 13 ]. Additionally, studies of this diatoms’ response to OA have found a variety of physiological responses even when the same strain was used [ 25 , 38 , 39 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The concentrations of oil used in this study were well below the 200 mg L -1 limit to simulate authentic spill conditions, as this has been a critique among some recent oil toxicity work [ 50 ]. Further, the DCEWAF treatments were prepared with EOEs more dilute than those used in previous studies [ 12 , 13 , 50 ] for two reasons. First, efforts were made to manipulate a similar oil concentration in WAF and DCEWAF, the latter of which, if not diluted, could be one to two orders of magnitude higher than WAF.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation